Pendampingan Siswa Peserta Olimpiade Sains Nasional dan Olimpiade Madrasah Indonesia di Madrasah Aliyah Negeri 1 Aceh Barat - Fajar Okta Widarta; Riza Ulhaq; Muhammad Farhan Putra Emil; Zahra Rodliyatam Mardliyah (Universitas Teuku Umar, 2026)
Olimpiade Sains Nasional (OSN) and Olimpiade Madrasah Indonesia (OMI) are two prestigious national science competitions that serve as benchmarks for the quality of education in schools across Indonesia. Madrasah Aliyah Negeri 1 Aceh Barat is one of the leading schools in Aceh Barat District, Aceh Province. The partner institution faces an issue of a lack of competent teachers to guide students in preparing for both activities. The aim of this community service activity is to provide learning assistance to the students of this school. The stages of this service activity consist of the planning stage, the implementation stage, and the evaluation stage. Based on the evaluation results, it appears that there has been an increase in knowledge and readiness among students in facing the OSN and OMI competitions. The author suggests that this activity should continue to be held every year and be emulated by other schools in Aceh Barat as a strategic effort to enhance students' readiness for these two prestigious events.